Additive Manufacturing Technology for Biomedical Components: A review - Zaharin, H.A. (Institute of Physics Publishing, 2018)
Over the last decades, additive manufacturing has shown potential application in ranging fields. No longer a prototyping technology, it is now being utilised as a manufacturing technology for giant industries such as the automotive, aircraft and recently in the medical industry. It is a very successful method that provides health-care solution in biomedical sectors by producing patient-specific prosthetics, improve tissues engineering and facilitate pre-operating session. This paper thus presents a brief overview of the most commercially important additive manufacturing technologies, which is currently available for fabricating biomedical components such as Stereolithography (SLA), Selective Laser Sintering (SLS), Selective Laser Melting (SLM), Fused Deposition Modelling (FDM) and Electron Beam Melting (EBM). It introduces the basic principles of the main process, highlights some of the beneficial applications in medical industry and the current limitation of applied technology. Â© Published under licence by IOP Publishing Ltd.